2019
DOI: 10.1590/s2175-97902019000117105
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of novel, mucoadhesive ofloxacin nanoparticles for ocular drug delivery

Abstract: The efficacy of conventional ocular formulations is limited by poor corneal retention and permeation, resulting in low ocular bioavailability. Mucoadhesive chitosan (CS)/ tripolyphosphatesodium (TPP) and chitosan (CS)/ tripolyphosphatesodium (TPP)-alginate (ALG) nanoparticles were investigated for the prolonged topical ophthalmic delivery of ofloxacin. A modified ionotropic gelation method was used to produce ofloxacin-loaded nanoreservoir systems. The ofloxacin-loaded CS/TPP and CS/TPP-ALG nanoparticles were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 34 publications
0
28
0
1
Order By: Relevance
“…NPs possess the merits of simple administration in fluid formula and swift dispersal through ocular tissues. The encapsulation of ophthalmic drugs in CS NPs and its use in solution formulations was found to significantly increase the residence time of antibiotic drugs in the precorneal area [111,125,126].…”
Section: Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…NPs possess the merits of simple administration in fluid formula and swift dispersal through ocular tissues. The encapsulation of ophthalmic drugs in CS NPs and its use in solution formulations was found to significantly increase the residence time of antibiotic drugs in the precorneal area [111,125,126].…”
Section: Nanoparticlesmentioning
confidence: 99%
“…NPs exhibited sizes in the range of 114 to 509 nm, while their size was proportionally influenced by the concentrations of CS and ALG. In vitro release studies evidenced a prolonged release over 24 h. Taghe et al exploited the ionic synergy among CS, TPP, and ALG to formulate nanoparticulate systems for the incorporation of ofloxacin, an anti-infection agent, and compared its ocular dynamic against CS/TPP NPs [126]. In both cases, roughly spherical particles with positive surface were formed, while in the case of CS/ALG/TPP NPs, increasing the ALG content led to less stable dispersions.…”
Section: Ionotropic Gelation With Other Polymersmentioning
confidence: 99%
“…The efficacy of ocular formulations is limited by poor corneal retention and permeation, resulting in low ocular bioavailability. Taghe and Mirzaeei [ 71 ] showed that mucoadhesive chitosan/sodium tripolyphosphate and chitosan/sodiumtripolyphosphate-alginate nanoparticles demonstrate prolonged topical ophthalmic delivery of ofloxacin. To date, the rapid clearance from the ocular surface has been a huge obstacle for using eye drops to treat glaucoma, since it has led to a short preocular residence time and low bioavailability.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] Unfortunately, topical dosage forms face some challenges, like low drug penetration to the different layers of the eye, high frequency of administration, low residence time, and systemic toxicities caused by longterm use. 9,10 Recently, many efforts have been made to improve topical ocular drug delivery by designing various novel drug delivery systems (NDDS), including liposomes, nanoparticles, nanoemulsions, nanosuspensions, micelles, nanofibers, etc. 10,11 These systems can be used to optimize ocular drug delivery.…”
Section: Introductionmentioning
confidence: 99%
“… 6 - 8 Unfortunately, topical dosage forms face some challenges, like low drug penetration to the different layers of the eye, high frequency of administration, low residence time, and systemic toxicities caused by long-term use. 9 , 10 …”
Section: Introductionmentioning
confidence: 99%